Pengaruh Rating dan Online Customer Review Terhadap Keputusan Pembelian Secara Online Pada Marketplace Shopee - Ambartiasari, Geta; Yusuf, Zulfan; Kasmaniar; Sarboini; Amri, Saiful (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The purpose of this study is to analyze the influence of online customer ratings and reviews on online purchasing decisions in the Shopee marketplace. With the development of e-commerce in Indonesia, consumers are increasingly relying on information from other users when making purchasing decisions. High ratings and positive reviews are intended to increase consumer trust and encourage purchases, while low ratings and negative reviews can reduce purchase intentions. The survey method is a survey distributed to Shopee users who shop. The resulting data is analyzed using regression analysis techniques to determine the relationship between rating variables, reviews, and purchasing decisions. This study shows that there is a significant positive influence between online customer ratings and reviews on purchasing decisions. The higher the rating and the more positive the reviews, the more likely consumers are to buy. This study helps business owners and marketers understand the importance of online reputation management and effective marketing strategies in the digital era. Therefore, sellers in the Shopee marketplace must pay attention to the quality of their products and services and actively manage customer reviews to increase the appeal of their products.